2018
DOI: 10.1016/j.omtn.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 Mediated Disruption of the Swedish APP Allele as a Therapeutic Approach for Early-Onset Alzheimer’s Disease

Abstract: The APPswe (Swedish) mutation in the amyloid precursor protein (APP) gene causes dominantly inherited Alzheimer’s disease (AD) as a result of increased β-secretase cleavage of the amyloid-β (Aβ) precursor protein. This leads to abnormally high Aβ levels, not only in brain but also in peripheral tissues of mutation carriers. Here, we selectively disrupted the human mutant APPSW allele using CRISPR. By applying CRISPR/Cas9 from Streptococcus pyogenes, we generated allele-specific deletions of either APPSW or APP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(112 citation statements)
references
References 38 publications
2
110
0
Order By: Relevance
“…The resulting increase in secreted Aβ40 and Aβ42 from this mutation leads to severe amyloid pathology (63). Using patient derived fibroblasts carrying the Swedish mutation, Gyorgy et al recently disrupted the cleavage site and observed a 60% decrease in Aβ production (22). Furthermore, the mutation was also targeted in both cultured primary cortical neurons and in vivo using Tg2576 adult mice that carry the APP SW mutation via adeno-associated virus mediated delivery of the Cas9 and sgRNA constructs into the hippocampus.…”
Section: Attacking the Disease At Its Source: Targeting The Genetic Mmentioning
confidence: 99%
“…The resulting increase in secreted Aβ40 and Aβ42 from this mutation leads to severe amyloid pathology (63). Using patient derived fibroblasts carrying the Swedish mutation, Gyorgy et al recently disrupted the cleavage site and observed a 60% decrease in Aβ production (22). Furthermore, the mutation was also targeted in both cultured primary cortical neurons and in vivo using Tg2576 adult mice that carry the APP SW mutation via adeno-associated virus mediated delivery of the Cas9 and sgRNA constructs into the hippocampus.…”
Section: Attacking the Disease At Its Source: Targeting The Genetic Mmentioning
confidence: 99%
“…Extensive work in mice and human cell lines has demonstrated that CRISPR can be used to correct mutations causing Duchenne muscular dystrophy, which recently advanced to restoring dystrophin protein expression in a canine model of the disease through systemic and intramuscular delivery of adeno-associated virus-encoded Cas9. 22 CRISPR-based treatments are also being developed for several brain diseases, 26,[97][98][99] eye diseases such as congenital blindness, and diseases of the liver. 100 The ideal genome-editing therapeutic would allow a single dose of a transiently active nuclease that can be administered systemically but with tissue-selective uptake, editing only the specific cell type in need of correction.…”
Section: Future Therapeutic Applicationsmentioning
confidence: 99%
“…They found specific disruption (i.e., indel formation) in 1.3% of APPswe alleles in all ( n = 5) injected mice. For comparison, the rate of indel formation was much higher in fibroblasts from human APPswe carriers, which carry only two copies in their genome (György et al, ). This proof‐of‐concept study highlighted the possibility of gene targeting as a potential avenue for treating familial AD and the potential role of AAVs herein.…”
Section: Gene Therapy Strategies In Ad Mouse Modelsmentioning
confidence: 99%